Physical Education Study Program Students Understanding of Healthy Living - Malasari, Citra Azhariat; Prihatmojo, Agung (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This research aims to determine the understanding of students in the FKIP UMKO physical education study program about healthy living. This research is a quantitative descriptive research. The method used is a survey with test and measurement techniques. The population in this study were all students of the FKIP UMKO physical education study program. The sample in this research was 48 students of the FKIP UMKO physical education study program class of 2023. The sampling technique is total sampling. The instrument used is a multiple choice test. The analysis technique used is quantitative descriptive statistics with percentages. The results of this research show that the 2023 FKIP UMKO physical education study program students' understanding of healthy living is in the very good category of 32 people or 66.67%, the good category is 10 people or 20.83%, the fair category is 3 people or 6, 25%, the less than 2 people or 4.17%, and the very less than 1 person or 2.08%.